Between Libido sciendi and critique of the speculative reason: Laura Bassi and the issue of scientific authority - Muceni, Elena (Itinerari, 2023)
Laura Bassi (1711-1778) was the first woman awarded the title of professor and to be granted a paid lectureship in Philosophia Universa (1732). From the very beginning of her research activity, she focused on the problem of the requirements and criteria that scientific theorising should satisfy. Having embraced physics as her favourite domain of research, she detected and understood the difficulties arising from the need to reconcile the sense of power of human reason and the appetite for knowledge with the adoption of rigorous epistemological criteria. Indeed, Bassi addressed this question in her first lectio publica, the text of which has survived among her manuscripts. In the article, we will question this document, in order to seize Bassi’s position on the legitimacy of the ambitions of human reason and on the gnoseological and theoretical conditions of scientific research.